Awareness Regarding Cervical Cancer among Women Attending a Selected Hospital in Lucknow, Uttar Pradesh: A Cross-Sectional Study. - Ankita Jacob; Shreyashi Dixit; Vaishnavi Tripathi; Shraddha Verma; Pooja; Jyoti Kumari Pal; Preeti Chaudhary (International Journal of Women's Health Nursing And Practices, 2025)
Cervical cancer continues to be a significant health concern, particularly in low- and middle-income countries like India, where it remains a leading cause of cancer-related deaths among women. Despite the availability of preventive measures such as the Human Papillomavirus (HPV) vaccine and screening techniques like Pap smears, a considerable gap in awareness persists. Limited knowledge of cervical cancer, its risk factors, symptoms, and preventive strategies hampers the effectiveness of early detection and vaccination efforts. This study aimed to assess the level of awareness regarding cervical cancer among women attending a hospital in Lucknow, Uttar Pradesh. A sample of 50 women, aged 20 to 45 years, was surveyed using a semi-structured interview schedule to evaluate their understanding of the disease, including its risk factors, symptoms, prevention methods, and available screening options.The results showed that a majority of the participants had insufficient knowledge about cervical cancer. Many were unaware of the significant role HPV infection plays in the development of cervical cancer, and a substantial number did not recognize the importance of the HPV vaccine. Additionally, most women lacked awareness about the various screening methods available, such as Pap smears, and were unsure of when and how often they should be screened. These findings highlight the critical need for targeted awareness programs and educational initiatives to fill the knowledge gaps among women, particularly in rural and underserved areas. In conclusion, the study emphasizes the necessity of improving cervical cancer awareness through comprehensive public health interventions. Enhancing knowledge about HPV, its link to cervical cancer, and preventive measures like vaccination and screening could significantly reduce the incidence and mortality rates associated with cervical cancer in India.
Keywords: Awareness; HPV; India; cervical cancer; health education; prevention; screening; women